Scaled Down Tunnel Testing for Comparison of Surface Support Performance - Kusui, Ayako (Curtin University, 2016)
A number of scaled down tunnels were prepared and tested to understand stress induced failures around underground excavations and surface support performance following violent failure. The experiment results corresponded well with full scale size tunnels. The failure mechanisms were examined and failure induced stress was evaluated as a function of the intact rock strength. Different surface support elements were compared and various surface support schemes were evaluated as an integrated system.